Spectral tracks in the ionosphere: Fast Fourier Transform analysis of seismo- ionospheric coupling through GPS Total Electron Content variations - Karatay, Secil; Cinar, Ali; Arikan, Feza; Arikan, Orhan (Springer Science and Business Media LLC, 2025)
Abstract
This study investigates seismo-ionospheric coupling through spectral analysis of Total Electron Content (TEC) variations using a specialized Fast Fourier Transform algorithm (IONOLAB-FFT). We analyze TEC data from dense GNSS networks across thirteen significant earthquakes (Mw 5.6-9.0) in diverse tectonic settings, including nine world events and four in Türkiye. Our analysis reveals consistent spectral patterns preceding earthquakes, characterized by systematic shifts toward lower dominant frequencies, narrowing bandwidths, and increasing durations as seismic events approach. These patterns show strong magnitude dependence: major earthquakes (Mw ≥ 8.0) exhibit dominant frequencies of 0.3–0.4 mHz with detectable ionospheric anomalies 4–5 days before the main shock, while moderate events (Mw 6.0–7.0) display higher frequencies (0.7–0.8 mHz) with precursors evident only 1–2 days prior. Pre-earthquake ionospheric signatures progressively transform from patterns resembling geomagnetically quiet conditions to those characteristic of disturbed periods, despite the absence of significant geomagnetic activity. Frequency-duration relationships demonstrate increasingly strong negative correlations as earthquakes approach, with spatial analysis showing clear epicentral focusing of anomalies. Secondary frequency peaks emerge 2–3 days before major events, potentially indicating different phases of the preparation process. The consistent patterns identified across diverse tectonic settings suggest that ionospheric precursors reflect fundamental physical processes related to pre-seismic strain accumulation. This research provides a quantitative framework for characterizing seismo-ionospheric coupling, offering potential applications for earthquake early warning systems through electromagnetic precursor monitoring.